11 Oncologic outcomes and role of adjuvant therapy in endometrial cancer patients with low volume metastasis in the sentinel lymph nodes: an international multi-institutional study. (13th November 2020) - Ghoniem, K; Dinoi, G; Larish, A; Zhou, X; AlHilli, M; Wallace, S; Wohlmuth, C; Baiocchi, G; Tokgozoglu, N; Raspagliesi, F; Buda, A; Zanagnolo, V; et al.
Abstract : Objective: To assess recurrence-free survival (RFS) and role of adjuvant therapy (ATx) in endometrial cancer with low volume metastasis (LVM) in sentinel lymph nodes (SLN). Methods: Patients with SLN LVM (≤2 mm) during 2010–2018 were retrospectively collected from 22 centers; stage IV, adnexal involvement, or unknown ATx were excluded. High-risk characteristics were grade (G) 3, non-endometrioid (NE) histology, lymphovascular invasion (LVSI), uterine serosal invasion (USI), or cervical stromal invasion. Results: 243 patients were included [131 isolated tumor cells (ITCs); 112 micro-metastasis (MM)]. The 186 patients who received ATx (external beam radiation therapy and/or chemotherapy) were more likely to be high-risk (75.3% vs. 38.6%) or have MM (55.9% vs. 14.0%) compared to patients without ATx. RFS was 78.1% (95% CI, 70.5–86.5%) at 4 years; median follow-up of patients without recurrence was 29.6 (IQR, 19.1–41.5) months. The 4-yr RFS was 83.8% (95% CI 73.1–96.1%) among 57 patients without ATx; no significant risk factors identified. In particular, there were 18 G1 non-high-risk patients with ITC and no ATx, of which only 1 has recurred. G3, NE, LVSI, and USI were associated with recurrence in patients receiving ATx (table 1 ). G3 or NE patients had poor outcome even with receiving ATx, the 4-yr RFS was 59.5% and 56.1%, respectively. Conclusion: In patients with SLN LVM who received ATx, G3, NE, LVSI, and USI were strong prognostic factors. ITCs patients with G1 and non-high-risk characteristics have good prognosis even without ATx; further analysis is needed, when this cohort matures, to know if ATx can be confidently spared.